PPH 21 Tax Calculation Application for Permanent Employees at The Bandung Regency Fire Service - Kirani, Sandra; Sudrajat, Jajat; Rachman, Rizal; Damayanti, Resti Aulia (P3M, STIE Pasundan, Bandung, Indonesia., 2024)
This study aims to create a software application that can accurately compute PPh 21 (income tax) for full-time employees at the Bandung Regency Fire Department. The development process will utilize an Object-Oriented Analysis and Design (OOAD) System Development approach. The primary aim of this study is to mechanize the computation of PPh 21 in compliance with relevant tax statutes while streamlining tax and payroll administration at the organization. The development methodology comprises five primary phases: requirements analysis, system design, implementation, testing, and assessment. During the requirements analysis phase, data is gathered through interviews, observations, and literature research to comprehend the system's functional and non-functional requirements. The system design step entails developing a system architectural design that includes class, use case, and interaction diagrams to guarantee that the system fulfills the given requirements. Implementation involves creating program code based on the design and integrating system components. The testing phase encompasses unit, integration, system, and acceptance testing to verify that the system operates as intended and is error-free. The evaluation phase incorporates the participation of end users to gather input on the system's usability, efficiency, and precision and introduce enhancements prior to its complete implementation. The research findings demonstrate that using this internet-based application can enhance the effectiveness and precision of tax computations, mitigate the likelihood of data loss, and facilitate heightened job efficiency at the Bandung Regency Fire Department. This application is anticipated to favorably impact tax and payroll management at the agency while also enhancing the quality of public services through digitalization and technological innovation.